Students’ perceptions of a scientific writing course: SFL Genre Pedagogy in an EFL context - Mirallas, Carolina Andrea (Signo, 2021)
Genre approaches to teaching have long been applied to improve students’ skills, and their effect has usually been assessed by looking into students’ productions. In this work, we examine students’ perceptions of the implementation of a genre-based writing course that incorporated tasks developed by the Reading to Learn Pedagogy (R2LP) (Rose & Martin, 2008) for the teaching of Scientific Research Articles (SRA) in an EFL context. A scientific writing course in English was offered for 8 weeks on a weekly basis to researchers and Ph.D. students in Argentina. They were asked to answer surveys after every class and once the course finished. Surveys were analysed considering ATTITUDE of the System of Appraisal (Martin & White, 2005), polarity and the entities evaluated. Joint writing and Detailed reading were entities frequently evaluated positively, mainly in terms of usefulness. Negatively appraised entities include contents and exercises, which were perceived as “difficult”. Our evidence suggests that the teaching of SRA writing to researchers through the R2LP in an EFL context is effective. More precisely, teacher-guided activities which were jointly carried out with students were found to be the most useful, making them suitable for a highly specialised audience like the one that participated in this study.